Correlates of Alcohol-Using Network Size Among Men Who Have Sex with Men in San Francisco, CA. Issue 2 (April 2021) - Garcia, Alex; Rowe, Chris; Turner, Caitlin; Santos, Glenn-Milo
Men who have sex with men (MSM) have a high prevalence of hazardous alcohol consumption. While network-level characteristics such as social network size have been indicated as upstream determinants of alcohol use in general population samples, no studies have examined factors associated with alcohol using network size (ANS), among MSM. This secondary analysis examined demographic, substance use, and sexual behavior correlates of ANS using data from a diverse sample of alcohol-using MSM in San Francisco ( N = 252). Associations were calculated using multivariable negative binomial regression, adjusting for age, race, education, and employment. The median ANS was 10. Factors associated with larger ANS in multivariable analyses included identifying as Hispanic/Latino, having completed a college education or higher, having a higher Alcohol Use Disorders Identification Test (AUDIT) score, having a greater number of sexual partners, polysubstance use, and being unaware of one's own HIV status. Factors associated with smaller ANS included being between 18 and 24 years of age, reporting a low income, and having any lifetime history of injection drug use. For MSM, ANS was associated with increased likelihood of hazardous alcohol use, as well specific individual-level substance use and sexual risk behaviors. These results highlight the role of ANS in hazardous alcohol consumption and sexually transmitted infection transmission among MSM. These results also indicate ways that research and intervention programs aimed at reducing alcohol use among MSM might be improved through network-based recruitment or engagement. Finally, these results suggest the need for further research on HIV-unknown MSM.